Model Pencantuman Asas Hukum Dalam Pembentukan Hukum Perikatan Nasional - Djumikasih, Djumikasih (UI Scholars Hub, 2022)
Indonesia is currently trying to draft a law of engagement. In the drafting process, there are differences of opinion as to whether the principles of binding law will be written explicitly or implicitly. Based on the results of the discussion, it can be concluded that, the nature of legal principles is a very important and fundamental thing, which comes from ethical values that exist in society, which is very useful because it is a direction guide, for the formation of legal norms and law enforcement itself. The function of legal principles is not only as a foundation, heart or bridge in the formation of binding law, but also functions as a compass for direction for the enforcement of binding law, because when there are problems in binding law that occur in the community while there are no rules governing it either in the law or in the agreement itself, the problem solving can be based on existing principles that function as a compass for direction for solving the problem. The right model for the inclusion of legal principles in the future Indonesian Bond Law is to be included explicitly to ensure legal certainty, justice and expediency. Based on the above conclusions, the author suggests the following: For the formulators of the Indonesian Law of Association, the inclusion of the principles of the future Indonesian Law of Association should be explicitly stated to ensure legal certainty for the parties and facilitate notaries and judges in enforcing the law of association. For judges, it is recommended that if they handle cases of binding law that have no legal basis, they can return to the existing principles of binding law. Notaries should pay attention to the principles of the law of engagement in drafting the deed of agreement requested by the parties.